Serious Fall Injury History and Adverse Health Outcomes After Initiating Hemodialysis Among Older U.S. Adults. (16th January 2018) - Bowling, C Barrett; Hall, Rasheeda K; Khakharia, Anjali; Franch, Harold A; Plantinga, Laura C
Abstract: Background: Although older adults with predialysis chronic kidney disease are at higher risk for falls, the prognostic significance of a serious fall injury prior to dialysis initiation has not been well described in the end-stage renal disease population. Methods: We examined the association between a serious fall injury in the year prior to starting hemodialysis and adverse health outcomes in the year following dialysis initiation using a retrospective cohort study of U.S. Medicare beneficiaries ≥ 67 years old who initiated dialysis in 2010–2012. Serious fall injuries were defined using diagnostic codes for falls plus an injury (fracture, joint dislocation, or head injury). Health outcomes, defined as time-to-event variables within the first year of dialysis, included four outcomes: a subsequent serious fall injury, hospital admission, post-acute skilled nursing facility (SNF) utilization, and mortality. Results: Among this cohort of 81, 653 initiating hemodialysis, 2, 958 (3.6%) patients had a serious fall injury in the year prior to hemodialysis initiation. In the first year of dialysis, 7.6% had a subsequent serious fall injury, 67.6% a hospitalization, 30.7% a SNF claim, and 26.1% died. Those with versus without a serious fall injury in the year prior to hemodialysis initiation were at higher risk (hazard ratio, 95% confidence interval) for a subsequent serious fall injury (2.65, 2.41–2.91), hospitalization (1.11, 1.06–1.16), SNF claim (1.40, 1.30–1.50), and death (1.14, 1.06–1.22). Conclusions: For older adults initiating dialysis, a history of a serious fall injury may provide prognostic information to support decision making and establish expectations for life after dialysis initiation.